Measures to Prevent Criminal Offences in the field of Informatisation and Communications in the Republic of Kazakhstan - Kambarov, Azamat; Karazhanov, Malik; Sabitov, Serik; Baigundinov, Yeldos; Temirgazin, Roman (Law, State and Telecommunications Review, 2024)
[Purpose] The relevance of the paper is due to the fact that the introduction of information technology has had an impact on the growth of economic crimes. The purpose of the study is to analyse the effectiveness of existing measures to prevent illegal acts in the field of informatisation and communications. [Methodology/approach/design] In the course of the study, the concept of cybercrime was covered, the signs and principles of implementation inherent in this category of offences were identified. This provided an opportunity to thoroughly analyse the essence and role of cybercrime in the field of informatisation and communications in the Republic of Kazakhstan. Statistical data on crimes for the period from 2018 to 2022 were examined, which allowed analysing the current situation and identifying the main problems in this area. The legal acts regulating the sphere of information technologies and communications in Kazakhstan were also examined. [Findings] Based on the analysis, recommendations to strengthen the system of countering information crimes were developed. The importance of taking preventive measures to prevent criminal offences in the field of informatisation and communications, especially in the context of rapid technological development, is due to the annual increase in the number of cybercrimes. The practical importance of the results obtained consists in the development of recommendations that will increase the effectiveness of combating criminal offences in the field of informatisation and communications in the Republic of Kazakhstan, improve the level of protection of society from cybercrime and have a positive impact on the national security system of the state.